Research on nonlinear automation for first order delays system - Roshanzamir, Ali; Piltan, Farzin; Jahed, Arman; Namvarchi, Saman; Nazari, Iman; Sulaiman, Nasri (Science and Engineering Research Support Society, 2015)
First order delay system (FODS) is in class of nonlinear systems. In these systems design control algorithms are very important. In this research nonlinear terms of incremental Proportional Integral Derivative (PID) algorithm is used to nonlinear modelfree integrate large amounts of control methodology in a single methodology. This work, proposes a developed method to design nonlinear based PID controller. In this methodology nonlinear model-free sliding mode algorithm help incremental PID to estimate and linearization of first order delay system. According to this research, the controller robustness improved based on nonlinear term of sliding mode algorithm and the chattering is reduced/eliminate based on PID incremental method.